Evaluasi umur sisa perkerasan kaku pada ruas jalan tol Solo-Ngawi - Mohammad Faizal Kelan Pambudi; Sri Sunarjono; Senja Rum Harnaeni (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Roads are the main infrastructure that aims to accelerate the growth of a region which results in the opening of social, economic, and cultural relations between regions. A good and stable road will affect the smooth flow of traffic. One of the toll roads that is indicated to have decreased pavement function due to various factors affecting damage is the Solo-Ngawi toll road. The evaluation of the remaining life of rigid pavement on the Solo-Ngawi toll road section aims to determine how much the remaining life value of rigid pavement on the toll road section and is used as a reference in determining the maintenance method. This research uses quantitative methods based on secondary data with reference analysis based on American Association of State Highway and Transportation Officials (AASHTO) 1993. It can be known based on the results of the evaluation analysis based on the 1993 AASHTO book, the CESAL value of the plan from the results of the analysis obtained a value of 22,913,047 ESAL, while for the Actual CESAL Based on each column, a value of 8,239,688 ESAL was obtained for the Solo-Ngawi direction and 4,270,023 ESAL for the Ngawi-Solo direction. From the two results above, it is stated that the remaining age for each route was obtained 64.04% for the Solo-Ngawi Direction and 81.37% for the Ngawi-Solo Direction. The benefits of this research can be known related to how old the remaining pavement of the Solo-Ngawi Toll Road section is so that it is expected to contribute as a reference for toll road managers to increase the road service period even more for vehicle users who choose the Solo-Ngawi toll road.